(untitled) (Revista Brasileira Multidisciplinar, 2010)
This paper discusses the application of environmental legislation in an Environmental Protection Area in the Guariroba Basin, Campo Grande, Mato Grosso do Sul, which accounts for 50% of water used in urban water supply in the city. The methodology of the research included a review of the bibliography related to public policies adopted in the area of Environmental Preservation and local analyses, assessing the validity and the effectiveness of enforcement in this area of environmental protection, considering legal, social and environmental points of view.The results indicate that environmental legislation is not being enforced and that there is a failure of public power, which does not monitor compliance with the standards that should govern this type of conservation unit, which suffers from erosion, silting of water resources, and continuous substitution of native vegetation by exotic species, such as pasture and eucalyptus, which threatens the region’s biodiversity and the water resources of the area.